Microfacies and Reservoir Space Characteristics of Carbonate Reservoir of the Ordovician Yingshan Formation in Northern Slope of Tazhong Uplift, Tarim Basin. (15th February 2023) - Ren, Ping
Abstract : As an important stratum of exploration in the Tarim Basin, which is the largest petroleum basin in China, Yingshan Formation has great potential. The relationship between the fine division of microfacies and reservoir space characteristics has not been systematically studied which restricts further exploration. On the basis of the analysis of core, thin section, logging data, imaging logging data (FMI), and field outcrop, the microfacies types and reservoir space characteristics of the Ordovician Yingshan Formation are systemically studied. The results show that (1) nine microfacies (Mf1-Mf9) and four microfacies associations (MA1-MA4) were identified within the Ordovician Yingshan Formation. MA1-MA2 represent a medium- to high-energy sedimentary background, and MA3-MA4 represent a medium- to low-energy sedimentary background. (2) Four reservoir space types were observed in the Yingshan Formation, which are dominated by fracture-dissolution pore type, followed by small dissolution vug type, seldom fracture type, and large-scale karst-cavity type. (3) High-energy microfacies are the material basis of favorable reservoirs. The high-energy microfacies associations are prone to small dissolution vug and fracture-dissolution pore types of reservoirs; large cave reservoirs can sometimes be developed in the high part of the sequence and form favorable reservoirs in the Yingshan Formation. The low-energy microfacies associations mostly appear as original strata or interlayer, but after the superposition of structural cracks, buried karsts, or epigenetic karsts, low-energy microfacies associations may form relatively small-scale fractured and fracture-dissolution pore types of reservoirs in this area.